2013
DOI: 10.1111/ajsp.12035
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and well‐being in low socio‐economic statusMalaysian adolescents: The role of resilience resources

Abstract: The present study examined the relationship between stressors, resilience resources, and well-being in adolescents with low socio-economic status in Malaysia. The specific aims were: (i) to differentiate between resilient and non-resilient adolescents in terms of their resilience resources; and (ii) to examine the role of resilience resources on the relationship between stressors and well-being. In a sample of 197 adolescents aged 12-16 years (mean = 13.77, sd = 1.49), results of the k-mean clustering techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 83 publications
(102 reference statements)
2
14
0
Order By: Relevance
“…Previous research methodologies use cross-sectionally designed studies and typically rely on retrospective reports [88-90]. These provide only partial snapshots of an individual’s capacity for resilient responding and can be subject to recall biases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research methodologies use cross-sectionally designed studies and typically rely on retrospective reports [88-90]. These provide only partial snapshots of an individual’s capacity for resilient responding and can be subject to recall biases.…”
Section: Discussionmentioning
confidence: 99%
“…Also perceived social support could be considered as a modifiable factor impacting significantly on psychological well-being in adolescents and young adults (Cicognani, 2011;Noor & Alwi, 2013), so we presumed that it could be a key element to improve their functioning.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that a good social support (Cicognani, 2011;Noor &Alwi, 2013) and use of adaptive coping strategies (Al-Bahrani et al, 2013) would protect against mood and cognitive problems, with a perceived general well-being.…”
Section: Aims and Predictionsmentioning
confidence: 99%
“…For example, scholars have demonstrated that social support predicts resilience amongst care workers (Wilks and Croom, ) and undergraduate students (Wilks and Spivey, ). Recent evidence also suggests that individuals with high resilience report greater SWB (Karreman and Vingerhoets, ; Noor and Alwi, ) and better mental health (Peng et al ., ; Pretsch, Flunger and Schmitt, ). We therefore suggest that the social support derived from business networks is likely to increase entrepreneurs’ resilience when confronted with challenges, thereby increasing SWB.…”
Section: Theory Developmentmentioning
confidence: 99%